Efektivitas Model PjBL – STEAM Berbasis Kearifan Lokal untuk Meningkatkan Kemampuan Berpikir Kritis dan Representasi Matematis Siswa - Hendri Wijaya; Huda , Nizlel; Kamid, Kamid; Syaiful, Syaiful (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study is a Systematic Literature Review (SLR) aimed at comprehensively examining the effectiveness of the Project Based Learning (PjBL) model integrated with STEAM (Science, Technology, Engineering, Arts, and Mathematics) based on local wisdom in improving students' critical thinking skills and mathematical representation. The review was conducted using the PRISMA protocol through searches of Scopus, Google Scholar, ERIC, and Garuda databases within the 2022–2024 timeframe. Of the articles identified, 20 articles met the inclusion criteria and were analyzed in depth. The results indicate that: (1) the PjBL-STEAM model based on local wisdom significantly improves students' critical thinking skills; (2) the local wisdom-based approach contributes positively to mathematical representation through connections between cultural contexts and abstract mathematical concepts; and (3) the synergy of all three components (PjBL, STEAM, local wisdom) creates an authentic and meaningful learning ecosystem that is more effective than separate application. These findings have important implications for the development of a contextual, character-based, and culturally-grounded mathematics curriculum in Indonesia.   Keywords: Critical Thinking, Local Wisdom, Mathematical Representation, Project  Based Learning, STEAM